(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Currently deployed ocean observatory buoys rely on solar, wind, and battery systems to power multiple sensors on the buoy and along the mooring line. These existing energy resources meet the system’s full power demand about 70% of the time. To satisfy the full power demands and prevent interruptions to data streams, Sandia National Laboratory is designing a new wave energy converter (WEC) that utilizes an inverted pendulum. The WEC is being designed to provide the buoy’s additional power needs with the goal of eliminating the need to periodically service the buoy and replace its depleted batteries. The WEC’s inverted pendulum is being supported vertically by a magnetic spring located in its axis thereby enabling the vertical pendulum’s mass to be supported by a low overall stiffness, this therefore allows the WEC to be tuned for impedance matching and greatly increases its power generation capability. The impedance matching of the WEC has been shown to maximize the WECs power generation capability. The magnetic torsion spring has an increased stroke length due to the use of a unique helical magnet arrangement and it is shown that the helical magnet arrangement is able to increase its operating stroke length to >130 degrees. The helical non-contact torque creation as well as over torque protection makes it particularly suitable for long-term continuous use within a WEC. The presented helical magnetic torsion spring uses a unique Halbach magnet arrangement that was shown to increase the field strength, and the constructed magnetic spring has a measured peak torque of 518Nm with a mass energy density of 29 J/kg. The full paper will focus on presenting the design, building and testing of the new type of helical magnetic torsion spring for integration into the inverted pendulum WEC. Experimental testing results will also be presented. The presented helical magnetic spring was designed to provide positive stiffness. However, it can be equally useful for integration into WECs that require negative stiffness capabilities.